A Study in LGBTQ Activism in Serbia and Russia after 1991: Different Countries, Common Issues?. Issue 1 (1st September 2017) - Ekaterina, Batueva; Vladimir, Đorđević
Abstract: This article is dedicated to examining the issue of LGBTQ activism in Serbia and Russia after 1991. Considering the fact that these countries were republics in two former socialist federal states, it is interesting to investigate the position of the LGBTQ community and conclude on the influence of this community in challenging the political and social status quo in both societies. Moreover, citizens of Serbia and Russia are understood to be predominantly Orthodox Christian, with generally pervasive patriarchal social attitudes, and this point makes a comparative perspective even more interesting. Hence, this article proposes to provide concise historical information on both communities in their respective states after 1991 when both the USSR and SFR Yugoslavia disappeared. Brief historical information will be presented only to introduce major developments in the existence of the said community and its position in both societies. Second, the article is aimed at discussing and comparing the major political and social constraints in both states on the LGBTQ community and its functioning. Lastly, the article seeks to present conclusions on whether the said community has so far had any influence in terms of being a possible "driver" of political and social changes, or it has remained but a mere object rather than subject in the social and political life.